Supplier Management Improvement in Aviation Industry: A Case Study of Beriev Aircraft Company - Elena Lvovna Makarova; Pavel Vladimirovich Pavlov (International Journal of Supply Chain Management, 2017)
In modern practice the problems of aircraft production take on a new character in an ever-changing geopolitical situation in the world. The aviation industry is one of the most promising trends for development of the national high-tech production. It requires special attention, as the potential is the source of a qualitatively new economic growth of countries in general and Russia in particular. In our research, we designated specific production of civil aircraft issues, which have, from the authors view point, the major influence on the industry product competitiveness for the aircraft factory. The purpose of this paper is to study and analyze domestic and international experience in supply chain management of the aviation industry to enhance the competitiveness of aircraft factory products. A case study applied at the aircraft factory to propose a method of selecting suppliers for improving the quality and competitiveness of the industry product. Based on undertaken analysis, the authors designated specific areas of strategy implementation for the supply chain management when entering new markets with products of aircraft factory. According to current situation at aviation industry, strategic scenario of quality management improvement with the priority of supply chain management processes is proposed after aircrafts mass production launch at aircraft factory.